Books and Monographs Received (Review of Economic Studies, 1936)
Journal Article Books and Monographs Received Get access The Review of Economic Studies, Volume 3, Issue 3, June 1936, Page 235, https://doi.org/10.1093/restud/3.3.235 Published: 01 June 1936